Optimization of electrochemical cells

CN115461906BActive Publication Date: 2026-10-09ALVEO ENERGY INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080094580.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-09
Filing Date
2020-12-09
Publication Date
2026-10-09
Estimated Expiration
2040-12-09

AI Technical Summary

Technical Problem

通过控制水含量来优化包括TMCCC材料的电化学电池的操作,可能比迄今为止通过常规电池制造技术所理解的更复杂

Benefits of technology

[0025] Other features, benefits, and advantages of the invention will become apparent upon reading this disclosure (including the specification, drawings, and claims).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115461906B_ABST
    Figure CN115461906B_ABST
Patent Text Reader

Abstract

A system and method to optimize an electrochemical cell by adjusting water content to be within a desired water content profile that includes sufficient coordinated water and reduces uncoordinated water below a desired target. A method to improve the performance of a battery containing one or more TMCCC materials can include providing an optimal amount of residual moisture (RM) to the electrode. There is too much RM and sufficient uncoordinated (including mobile) water such that battery performance can be reduced. Too low of RM, TMCCC electrode performance is reduced. But by fine tuning the RM of the electrode, an optimal balance of electrode and battery performance characteristics can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications

[0002] This application claims priority to U.S. Application 16 / 708,213, filed December 9, 2019, the contents of which are incorporated herein by reference in their entirety for all purposes. Technical Field

[0003] The present invention generally relates to electrochemical cells using coordination compounds in one or more electrodes, and more specifically, but not exclusively, to improving the operation of electrochemical cells by controlling the water content of electrochemical cells having one or more electrodes comprising one or more transition metal cyanide coordination compounds. Background Technology

[0004] The topics discussed in the Background section should not be considered prior art, but merely as a result of their mention in the Background section. Similarly, problems mentioned in or related to the topics in the Background section should not be assumed to have been previously recognized in the prior art. The topics in the Background section merely represent different methods and may themselves be inventions.

[0005] Electrochemical batteries are generally considered to use electrode materials belonging to one of two categories: (i) materials containing an aqueous electrolyte or (ii) anhydrous electrolyte. Examples of the former include lead-acid batteries and nickel / metal hydride batteries. Examples of the latter include lithium-ion batteries. It is well known that in batteries containing anhydrous electrolytes, any trace water impurities, even at low concentrations of parts per million, will degrade battery performance in one or more performance metrics. Therefore, the solution is to implement a rigorous drying chamber process for preparing component materials in batteries and battery assemblies. Efforts are made to dry the electrode components as thoroughly as possible to remove as much trace water as possible.

[0006] For example, each type of cell material is dried independently in a dedicated room (drying chamber) with water / moisture control. These individually dried materials are then taken to an assembly area to produce individual cells, which are then assembled into stack assemblies (cell stacks). This process increases the complexity, risk, and resource costs of producing these cell stacks.

[0007] Regarding the water content of batteries containing anhydrous electrolytes, see, for example, reference [1] - Imhof, reference [1] Figure 6 It is shown that an increase in ppm-level water impurities reduces the reversibility of the charging / discharging process of graphite electrodes in lithium-ion batteries. This is the conclusion on page 1087 of reference [1]: "Experiments using EC / DMC-based electrolytes containing different amounts of water have shown that the Li+ intercalation process becomes less reversible with increasing water content."

[0008] Some materials used as electrodes in electrochemical cells may include transition metal cyanide coordination compounds (TMCCCs). Reference [2] considers TMCCC materials to belong to the (ii) anhydrous class. Reference [2] describes a method for drying TMCCC electrode materials to improve battery performance. In particular, Reference [2] teaches a manganese hexacyanoferrate (MnHCF) TMCCC electrode material, which is dried to a sufficiently low residual moisture (RM) to remove all interstitial water. When this occurs, the MnHCF material undergoes a phase transition from cubic to rhombohedral phase (Column 8). When this phase transition occurs, all the electrochemical capacity of the MnHCF electrode is captured in a single charge-discharge plateau. Having a single reaction plateau is ideal because it allows the electrochemical cell to operate over a narrower voltage range, reducing the cost and complexity of integrating the cell into other electronic systems. To achieve this result, Reference [2] further describes the use of a vacuum drying method with a vacuum pressure below 0.1 Torr (Column 7 and claim 1).

[0009] Claim 1 of reference [2] claims a TMCCC in which a range of water may be present (z in the range of 0 to 3.5). However, column 8 describes in detail that all interstitial water must be removed from the structure to obtain a rhombohedral phase with a single reaction plateau. Furthermore, in reference [3], the same inventors show that the rhombohedral phase with a single reaction plateau is completely anhydrous. Throughout reference [3], the single plateau phase is referred to as "anhydrous" in contrast to the "hydrated" phase with two reaction plates. Furthermore, in the supplementary information of reference [3], Figure S2 shows that the "anhydrous" phase contains zero water. In other words, the MnHCF sample undergoing the phase transition does not contain water tightly bound to the lattice when dehydrated, and all water present before drying is interstitial. Therefore, those skilled in the art will consider the teachings of references [2] and [3] to indicate that a rhombohedral single plateau phase is achieved when all water is removed from the structure, or in the case related to claim 1 of reference [2] (when z = 0).

[0010] It should be noted that “anhydrous” as used in reference [3] is not a commonly used term. It is usually defined as the anhydrous form of a material that normally contains water. A reasonable interpretation of reference [3] is that “anhydrous” is synonymous with “anhydrous”, which means a substance that contains no water or only a negligible amount of water as a trace impurity. Conversely, if reference [3] refers to vacuum-dried MnHCF as “dehydrated,” it should generally be understood that some or all of the water originally present in the material has been removed. Considering Figure S2 as described above, the authors use “anhydrous” instead of “dehydrated” to indicate that all water has been removed from the material.

[0011] Contrary to these public disclosures, TMCCC materials used as electrodes in electrochemical cells may not exclusively fall into these aqueous or anhydrous categories. Optimizing the operation of electrochemical cells incorporating TMCCC materials by controlling water content may be more complex than understood so far through conventional battery manufacturing techniques.

[0012] A system and method for optimizing electrochemical cells including electrodes using coordination compounds is advantageous. Summary of the Invention

[0013] A system and method for optimizing electrochemical cells including electrodes using coordination compounds are disclosed. The following overview of the invention is provided to facilitate understanding of some technical features related to the management of water content in electrodes including TMCCC materials, and is not intended as a complete description of the invention. A full understanding of various aspects of the invention can be obtained by considering the entire specification, claims, drawings, and abstract as a whole. The invention is applicable to other coordination compounds besides TMCCC materials, particularly those including water disposed at crystal structural sites and water disposed in a non-coordinated manner.

[0014] One embodiment of the present invention includes a novel battery pack based on an electrode comprising a transition metal cyanide coordination compound (TMCCC) material. These TMCCC materials naturally contain water. Some of the water contained therein is tightly bound within the crystal structure of the material (e.g., lattice bonding), and some interstitial water can reversibly move into and out of the electrode during charging and discharging, and some water can bind to various surfaces of the particles of the TMCCC material (such non-lattice bonding is collectively referred to herein as non-coordinated water). Some non-coordinated water may flow into and out of the TMCCC material and may then undergo chemical or electrochemical reactions with other battery components, potentially leading to a reduction in battery performance. Based on references [1], [2], and [3], it is expected that removing all water from the TMCCC material would enhance the performance of the electrode and the battery by eliminating these undesirable reactions. However, surprisingly, complete dehydration of the TMCCC material, including the removal of water tightly bound within the crystal structure, has been shown to reduce the performance of the completely dehydrated TMCCC material. It should be noted that references [1], [2], and [3] do not appear to teach or discuss non-coordinated water, including any water other than interstitial water. Other types of water may include surface water as well as water present in any pores (including micropores) within the TMCCC structure. There are several different reasons why these references do not discuss the content of this type of water, for example, it may be considered irrelevant / inappropriate or its presence may be misunderstood.

[0015] One embodiment of the present invention describes a method by which the performance of a battery comprising one or more TMCCC materials can be optimized by providing an optimal amount of residual moisture (RM) to the electrode. Too high an RM, along with sufficient uncoordinated (including mobile) water, can degrade battery performance. Too low an RM results in degraded TMCCC electrode performance. However, by fine-tuning the RM of the electrode, an optimal balance between electrode and battery performance characteristics can be achieved. The moisture content can be adjusted by partial dehydration and / or partial reabsorption of water to obtain the desired RM, which is greater than that of anhydrous materials but can be less than the water content of freshly synthesized, unprocessed TMCCC materials. This intermediate amount or concentration of electrode water content is one aspect of some embodiments of the present invention.

[0016] Embodiments of the present invention may include improved manufacturing. Some processing steps can be simplified because fewer corrosive moisture removal processes may be required. For example, one aspect of the invention involves assembling an entire electrochemical cell or an assembly of such cells into a battery stack, one or more cells including at least one electrode having a TMCCC material with a water content exceeding a desired range, and then optimizing the water content in the assembled cell or battery stack. This differs from individually dehydrating / hydrating materials and then assembling them using the dehydrated / hydrated materials.

[0017] One embodiment of the invention may include a method for optimizing battery performance, comprising dehydrating / hydrating at least one electrode to a controlled residual moisture content. Other embodiments may include a target range of residual moisture content, dehydration / hydration conditions / apparatus, etc.

[0018] One embodiment of the present invention may include a material composition for an electrochemical cell, wherein one or more electrodes contain a set non-zero amount of water, wherein the specific amount of water (i.e., greater than zero and less than a threshold) is different from an electrochemical cell having one or more electrodes containing a TMCCC material having an undefined amount of water n>0.

[0019] One embodiment of the present invention may comprise an electrode containing a coordination compound, an electrochemical cell having one or more electrodes made of this material, and / or an electrochemical cell stack comprising one or more such electrochemical cells, wherein the coordination compound (e.g., a TMCCC material) has a crystal structure, and the crystal structure contains residual moisture (RM) present in at least two forms: the first form is bound in the crystal structure, and the second form is water free from the crystal structure (e.g., non-coordinating water), wherein the desired RM comprises the first form that is completely retained to maintain the crystal structure and an optimally selected amount of the second form. The water content of the TMCCC material will always be greater than zero, but has a maximum value that is necessary or desired for the crystal / lattice structure. The presence of additional non-coordinating water in TMCCC exceeding the amount included in the desired RM is considered an undesirable impurity (the presence of which reduces performance) and is desirably reduced together with other undesirable impurities.

[0020] One embodiment of the present invention comprises improving the performance of an electrochemical cell, wherein the electrochemical cell has at least one electrode comprising a TMCCC material whose water content is outside a preferred water range, the preferred water range comprising a sufficient amount of the first form of residual moisture to maintain the crystal structure and electrochemical performance of the material, and by adjusting the total residual moisture of one or more electrodes into the preferred water range, the amount of the second form of residual moisture is minimized to reduce non-coordinating water or other non-crystalline water as much as possible.

[0021] One embodiment of the present invention may comprise a method of manufacturing an electrochemical cell, the electrochemical cell comprising a cell stack, the cell stack comprising one or more anodes, one or more separators and one or more cathodes, the method comprising a dehydration / hydration step, in which the cell stack is exposed to a predetermined temperature and pressure for a period of time, wherein a first of the anode or the cathode comprises a first TMCCC material and comprises a first residual moisture RM1, and wherein the dehydration / hydration step reduces the moisture content of the TMCCC-containing electrode to RM2 < RM1, and wherein the first TMCCC material is represented by formula A x P y [R(CN)6] z (H2O) n wherein A comprises one or more alkali metal cations, P and R each comprise one or more divalent or trivalent transition metal cations, 0.5 < z < 1, n = 6*(1-z) + m, n > 0, 6*(1-z) is the amount of lattice-bound water, m is the amount of non-coordinating water, and m ≥ 0.

[0022] A method for manufacturing a battery stack for an electrochemical cell, the electrochemical cell comprising a plurality of layers, each layer comprising an anode electrode, a cathode electrode and a separator disposed therebetween, wherein all anodes in the plurality of layers are in electronic communication, and wherein all cathodes in the plurality of layers are in electronic communication, and wherein at least one electrode comprises a coordination compound material comprising a water content, the water content comprising a degradation of a set of electrochemical properties present during electrochemical cycling of the battery, the method comprising a) manufacturing a set of electrodes, wherein at least a subset of the set of electrodes comprises an anode electrode and a cathode electrode having a coordination compound containing a water content; b) assembling a battery stack using the subset of electrodes comprising a water content, the battery stack assembly b) producing an assembled battery stack having an assembled subset of electrodes comprising a water content; and c) exposing the assembled battery stack having the assembled subset of electrodes comprising a water content to a water conditioning process configured to adjust the water content of the electrodes of the electrode subset to be within a conditioned water content; wherein the conditioned water content comprises a reduction of a set of electrochemical properties present during electrochemical cycling of the assembled battery stack.

[0023] A method for manufacturing a battery stack for an electrochemical cell, the battery stack comprising a plurality of layers, each layer comprising an anode electrode, a cathode electrode and a separator disposed therebetween, wherein all anodes in the plurality of layers are in electronic communication, and wherein all cathodes in the plurality of layers are in electronic communication, and wherein at least one electrode comprises a coordination compound material having residual moisture outside a desired residual moisture distribution, the method comprising a) assembling the battery stack while the residual moisture of at least one electrode in each electrochemical cell is outside a desired residual moisture distribution; and then: b) exposing the battery stack to a water conditioning process to adjust the residual moisture of at least one electrode in each electrochemical cell to be within a desired residual moisture distribution.

[0024] Any embodiment described herein may be used alone or in any combination with each other. The invention covered herein may also include embodiments that are only partially mentioned or implied, or not mentioned or implied at all, in this brief summary or abstract. While various embodiments of the invention may be inspired by various deficiencies of the prior art, which may be discussed or implied in one or more places in the specification, embodiments of the invention need not address any of these deficiencies. In other words, different embodiments of the invention may address different deficiencies discussed in the specification. Some embodiments may address only some or only one of the deficiencies that may be discussed in the specification, and some embodiments may not address any of these deficiencies.

[0025] Other features, benefits, and advantages of the invention will become apparent upon reading this disclosure (including the specification, drawings, and claims). Attached Figure Description

[0026] The accompanying drawings further illustrate the invention and, together with the detailed description of the invention, serve to explain the principles of the invention. In the drawings, the same reference numerals refer to the same or functionally similar elements in the various individual views, and these drawings are incorporated in and form a part of the specification.

[0027] Figure 1 The specific capacity of an electrode containing sodium manganese hexacyanomanganate TMCCC anode material is shown as a function of the residual moisture content of the electrode after drying.

[0028] Figure 2 The total impedance and charge transfer resistance of an electrode containing sodium manganese hexacyanomanganate TMCCC anode material are shown as a function of residual moisture in the electrode after drying.

[0029] Figure 3 Electrochemical impedance spectroscopy of an electrode containing sodium manganese hexacyanomanganate TMCCC anode material is shown as a function of residual moisture in the electrode after drying.

[0030] Figure 4 The total impedance and charge transfer resistance of an electrode containing sodium manganese iron hexacyanate ferric oxide TMCCCC cathode material are shown as a function of residual moisture in the electrode after drying.

[0031] Figure 5 The specific capacity of the capacitive electrodes of a full cell comprising a sodium manganese hexacyanomanganate TMCCC anode and a sodium manganese iron hexacyanomanganate TMCCC cathode is shown, which decreases as the weighted average residual moisture of the two electrodes decreases.

[0032] Figure 6 The power density and energy density of the capacitive electrodes of a full cell comprising a sodium manganese hexacyanomanganate TMCCC anode and a sodium manganese iron hexacyanomanganate TMCCC cathode are shown. The power density and energy density decrease as the weighted average residual moisture of the two electrodes decreases.

[0033] Figure 7 Electrochemical impedance spectroscopy of a full cell containing sodium manganese hexacyanomanganate TMCCC anode and sodium manganese iron hexacyanoferrate TMCCC cathode is shown as a function of the weighted average residual moisture of the two electrodes.

[0034] Figure 8 The lifespan of a full cell containing a sodium manganese hexacyanomanganate TMCCC anode and a sodium manganese iron hexacyanoferrate TMCCC cathode is shown during a float test at 45°C.

[0035] Figure 9Tables showing the residual moisture, coordinated water, and non-coordinated water of selected examples of the materials presented herein before and after drying are shown; and

[0036] Figure 10 The table shows the composition of various materials based on moles, and also includes calculations of residual moisture, coordinated water and non-coordinated water based on mass percentage. Detailed Implementation

[0037] Embodiments of the present invention provide systems and methods for optimizing electrochemical cells including electrodes using coordination compounds. The following description is provided to enable those skilled in the art to make and use the invention, and is provided in the context of the patent application and its claims.

[0038] Various modifications to the preferred embodiments, as well as the general principles and features described herein, will be apparent to those skilled in the art. Therefore, the invention is not limited to the illustrated embodiments, but is accorded the widest scope consistent with the principles and features described herein.

[0039] definition

[0040] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which the general concepts of this invention pertain. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having meanings consistent with their meanings in the relevant technical context and in the context of this disclosure, and will not be interpreted in an idealized or overly formal sense unless expressly defined herein.

[0041] The following definitions apply to some aspects described with respect to certain embodiments of the invention. These definitions are also open to extension herein.

[0042] As used herein, the term "or" includes "and / or" and the term "and / or" includes any and all combinations of one or more associated listed items. When preceding a column element, expressions such as "at least one" modify the entire column element and do not modify individual elements within that column.

[0043] As used herein, the singular terms “a,” “an,” and “the” include plural indicators unless the context clearly indicates otherwise. Thus, for example, a reference to an object may include multiple objects unless the context clearly indicates otherwise.

[0044] Furthermore, as used in this specification and the appended claims, the meaning of "in..." includes both "in..." and "on..." unless the context clearly specifies otherwise. It should be understood that when an element is referred to as being "on" another element, it can be directly on the other element, or there can be an intermediate element between them. Conversely, when an element is referred to as being "directly on another element", there is no intermediate element.

[0045] As used herein, the term "set or group" refers to a collection of one or more objects. Therefore, for example, a set of objects can include a single object or multiple objects. A set of objects can also be referred to as members of that group. Objects in a set can be the same or different. In some cases, objects in a set can share one or more common properties.

[0046] As used herein, the term "adjacent" means close or adjacent. Adjacent objects may be spaced apart from each other, or they may be in actual or direct contact with each other. In some cases, adjacent objects may be coupled to each other or may be integrally formed with each other.

[0047] As used herein, the terms “connection,” “linked,” and “attachment” refer to a direct attachment or link. The connected objects do not have, or substantially do not have, any transitional objects or groups of objects as indicated by the context.

[0048] As used in this article, the terms “coupled,” “coupledly,” and “coupled” refer to an operational connection or link. Coupled objects can be directly connected to each other or indirectly connected to each other, such as through a group of transitional objects.

[0049] The term "about" is used applicable to all numerical values, whether explicitly stated or not. This term generally refers to a range of numbers that a person skilled in the art would consider a reasonable deviation from the stated value (i.e., having an equivalent function or result). For example, the term can be interpreted as including a deviation of ±10% from a given value, provided that such deviation does not alter the final function or result of the value. Therefore, a value of about 1% can be interpreted as a range of 0.9% to 1.1%.

[0050] As used herein, the terms “substantially” and “substantially” refer to a considerable degree or extent. When used in conjunction with an event or environment, the term can refer to a situation in which the event or environment occurs precisely or in a situation in which the event or environment occurs in a close approximation, for example, considering the typical tolerance level or variability of the implementation described herein.

[0051] As used herein, the terms “optional” and “optionally” mean that the event or situation described below may or may not occur, and the description includes both the scenario in which the event or situation occurs and the scenario in which the event or situation does not occur.

[0052] As used herein, the term "size" refers to a characteristic dimension of an object. Thus, for example, the size of a spherical object can refer to the diameter of that object. In the case of a non-spherical object, the size of the non-spherical object can refer to the diameter of the corresponding spherical object, wherein the corresponding spherical object exhibits or has substantially the same set of specific differentiable or measurable properties as the non-spherical object. Thus, for example, the size of a non-spherical object can refer to the diameter of a corresponding spherical object that exhibits substantially the same light scattering or other properties as the non-spherical object. Optionally, or in combination, the size of a non-spherical object can refer to the average of various orthogonal dimensions of the object. Thus, for example, the size of a spherical object can refer to the average of the major and minor axes of the object. When a set of objects is referred to as having a specific size, it is conceivable that the objects can have a size distribution around said specific size. Thus, as used herein, the size of a set of objects can refer to the typical size of the size distribution, such as the average size, median size, or peak size.

[0053] As used herein, the term "residual moisture" for coordination compounds, particularly TMCCC materials, refers to the total water content of the TMCCC. Residual moisture consists of the total water mass divided by the total dry mass of the TMCCC material (the mass of metals, CN groups, and any other chemicals such as chelates). For example, in the case of 100g of TMCCC with a dry mass and a total water content of 10g, the residual moisture is calculated as 10g water / 100g dry mass = 10%.

[0054] As used herein, the water content of coordination compound materials is complex and refers to a hybrid residual water state that identifies lattice-bound water content (e.g., coordination water), preferably just sufficient to avoid degrading the desired electrochemical properties of the coordination compound material while minimizing amorphous water content (e.g., non-coordination water). Amorphous water, sometimes referred to herein as non-coordination water, can exist in various forms, primarily as interstitial water and / or water bound to the particle surface of the coordination compound material and / or water present in any pores or micropores within the TMCCC particles. Non-coordination water exceeding a threshold in the optimally selected residual water content is considered an undesirable impurity, reducing the desired electrochemical performance, while lattice-bound water is considered necessary and desirable. Materials in this hybrid water content state are neither aerated nor anhydrous in bulk. As discussed herein, without adequate care, water management processes (e.g., drying) may not adequately distinguish between coordination and non-coordination water in the coordination compound material. The coordination compound materials discussed herein can be used in systems comprising an aqueous electrolyte that can affect the water content of the coordination compound material after assembly or during use. The coordination compound materials discussed herein can also be used in systems comprising an initial anhydrous electrolyte that can affect the water content of the coordination compound material after assembly or during use, and which can become aqueous during or after assembly or during use due to the partial or complete release of non-coordinated water from the coordination compound material. The electrolyte is preferably an anhydrous electrolyte, which allows for better control of the water content of the electrode material. The manufacture of coordination compounds typically results in an excess of water associated with the material, which typically includes non-coordinated water as defined herein. Sometimes the water content may be too low, sometimes characterized by the removal of coordinated water. Therefore, it is preferable to adjust the water content to a desired range with sufficient coordinated water to achieve the desired electrochemical properties while minimizing non-coordinated water within the target range. Coordination compounds whose residual water is adjusted to a desired range of non-degradable water content are referred to herein as water-adjusted coordination compound materials. Similarly, coordination compounds whose residual water exceeds this range are referred to herein as water-unadjusted coordination compound materials.

[0055] As used herein, in the context of electrolytes used in electrochemical cells, the term "aqueous" refers to an electrolyte comprising water as a solvent and one or more dissolving materials, wherein the aqueous solvent has a concentration greater than 0.5%.

[0056] As used herein, in the context of electrolytes used in electrochemical cells, the term "anhydrous" refers to an electrolyte that includes solvents other than water, with water as a trace impurity having a concentration of less than 0.5%.

[0057] As used herein, in the context of removing water from a material, the term "drying" refers to removing water to the greatest extent possible, consistent with the drying process, leaving water as a trace impurity, the concentration of which is limited by the actual drying process used. Drying changes the material to an anhydrous state (therefore, dried material is an anhydrous material).

[0058] As used herein, in the context of altering the concentration of water in a material, the term "dehydration" refers to the controlled reduction of the moisture content to a desired level greater than trace impurities. In contrast to drying, dehydration aims to retain water as an essential component of the material, for example, retaining coordinated water while removing non-coordinated water.

[0059] As used herein, in the context of altering the concentration of water in a material, the term "hydration" refers to the controllable increase of the water content within a target range to a level greater than trace impurities but less than the material's water content, for example, by adding coordinated water without adding non-coordinated water.

[0060] As used herein, in the context of altering the concentration of water content in a coordination compound (e.g., a TMCCC material), the term "adjustment" refers to dehydrating or hydrating the material to achieve a desired concentration of coordinated water that enables the desired electrochemical properties without unnecessarily dissociated or other water content. Adjustment of water content aims to optimize toward zero or near-zero dissociated water without losing any coordinated water. One approach to considering water content adjustment is to take into account the mass fraction of water in the TMCCC material, including both dissociated and lattice-coordinated water before and after adjustment.

[0061] This paper describes a novel class of battery packs based on electrodes comprising transition metal cyanide coordination compound (TMCCC) materials. These TMCCC materials naturally contain water. Some of the water contained therein is tightly bound within the crystal structure of the material, and some uncoordinated water can reversibly migrate into and out of the electrode during charging and discharging. The water leaving the TMCCC material can then undergo chemical or electrochemical reactions with other battery components, leading to a degraded battery performance. Therefore, it is anticipated that removing water from the TMCCC material will enhance electrode and battery performance by eliminating these undesirable reactions. However, complete dehydration of the TMCCC material, including the removal of water tightly bound within the crystal structure, degrades the material's performance. Embodiments of the invention set the water content at a preferred level, which includes sufficient water for the crystal structure while simultaneously minimizing / reducing uncoordinated water.

[0062] The method taught in reference [2] has drawbacks in terms of efficiency and the performance of the resulting battery pack. For example, the method in reference [2]... Figure 8-9 As shown, a first drying step is performed after the synthesis of the material. Figure 8This results in the formation of anhydrous (z=0) rhombohedral phase. Alternatively, the drying step can be performed after the material has been processed into electrodes. Figure 9 TMCCC materials readily reabsorb water from the surrounding environment, such as the humidity in the air where they are stored. All processing steps after drying the TMCCC materials to the desired stage must be performed in a drying chamber, which increases the cost and complexity of those steps. Therefore, to minimize the cost and complexity of manufacturing batteries containing one or more TMCCC electrodes, the drying step should be performed after as many other processing steps as possible. Furthermore, in the case of a battery containing two TMCCC electrodes (anode and cathode), performing a separate drying step for each of these two materials, or for each of these two electrodes individually, is more complex than performing a single drying step on the assembled battery.

[0063] This document discloses a simpler method for manufacturing a battery comprising two TMCCC electrodes, the method comprising processing TMCCC material into electrodes, assembling these electrodes into a battery stack (a stack of anode, separator, and cathode electrodes), and then performing a single drying step on the battery stack to simultaneously dry both electrodes. This is one embodiment of the invention.

[0064] The performance of an electrochemical cell containing TMCCC electrodes depends on the amount of water contained in these electrodes. Contrary to the teachings of references [2] and [3], some embodiments of the present invention illustrate that the following is not necessarily true: removing all water from a set of TMCCC electrodes will result in optimal battery performance. For example, the impedance of a TMCCC electrode increases as its RM decreases through a more aggressive drying process. Higher electrode impedance reduces the energy efficiency and power capability of the battery. Depending on the application in which the battery is used, different performance metrics are more important than others. For applications where high energy efficiency is important, a non-zero RM in the TMCCC electrode is optimal. On the other hand, as taught in reference [2], for applications where operating the battery pack within a narrow voltage range is important, it is necessary to dry the TMCCC electrodes to the point that they are “anhydrous” (RM = 0). The teachings of reference [2] suggest that better performance can be provided within a narrow range for specific applications and device requirements than by maintaining RM within a preferred non-zero range.

[0065] Embodiments of the present invention may include a process for partially or completely removing non-coordinated water from a TMCCC structure, but not lattice-bound water. This dehydration process can be performed on individual TMCCC materials or electrodes containing them, or on a fully assembled battery stack. In some cases, the TMCCC material may not have sufficient water for its lattice structure; therefore, one aspect of the present invention allows for the addition of water to meet lattice requirements without adding non-coordinated water.

[0066] A first advantage of some embodiments of the present invention is that, by removing a controlled amount of noncoordinate water while leaving lattice-bound water in the material, the performance of the cell can be fully optimized for a variety of performance metrics, including energy efficiency, cycle life, and other metrics.

[0067] A second advantage of some embodiments of the invention relates to the mechanical stability of the electrodes during the drying process. Drying coated electrodes to a completely anhydrous state requires prolonged exposure to high temperatures (typically >130°C) and vacuum. Unfortunately, at high temperatures, the polymer binder contained in the porous electrodes softens. This allows any stress that has accumulated in the electrodes during processing to be released, resulting in electrode deformation by curling and loss of planarity. Subsequent processing steps, such as electrode stacking, require punched electrodes that are planar. Deformed or curled electrodes are more difficult to process and can lead to defects and / or yield loss. However, when the target RM of the TMCCC electrode is significantly higher than zero (about 4% or higher), less aggressive drying conditions (<100°C) are required, and less electrode deformation occurs during drying to the target RM. Furthermore, mechanical fasteners can be used to compress one or more electrodes or battery stacks, thereby achieving uniform temperature, drying rate, and final RM. These mechanical fasteners also provide mechanical stability to the electrodes or battery stacks. Therefore, for large batches of tens or even hundreds of electrodes or battery stacks, these fasteners result in a consistent and uniform RM, which leads to higher quality products. In addition, these fixtures reduce or even eliminate mechanical deformation that occurs during the drying process, during which the electrodes or battery stacks are not mechanically constrained.

[0068] A third advantage of some embodiments of the invention is that the drying step can be performed on a fully assembled battery stack by drying only to an intermediate amount of RM, including retaining all lattice-bound water. By drying the entire battery stack, fewer subsequent processing steps must be performed in a low-RH atmosphere, thereby reducing the cost and complexity of electrode fabrication and battery assembly processes. Furthermore, in cases where the battery stack includes separators, which are Z-folded between the perforated electrodes and optionally wound around the outside of the battery stack, the mechanical stiffness provided by the separators limits deformation and curling of the electrodes during drying. This reduces the risk of defects associated with electrode deformation and improves yield.

[0069] Embodiments of the present invention may include a method for drying a TMCCC electrode to an optimal RM, at which one or more cell performance metrics reach their optimal values. The TMCCC material has the general chemical formula A. x P y [R(CN) 6-p (NC) p ] z(H2O) n In this formula, A is one or more mobile cations, such as Li+, Na+, or K+, P and R are each one or more transition metal cations in the 1+, 2+, 3+, or 4+ state, including but not limited to Cr, Mn, Fe, Ni, Cu, and Zn, and H2O represents a water molecule. The general chemical formula is usually normalized to y = 1, and in this case, typical compositions include 0 ≤ x ≤ 2, 0.5 ≤ z ≤ 1, 0 ≤ p ≤ 3, and 0 ≤ n ≤ 4. The water content of TMCCC materials can also be expressed as a percentage of the total mass of the material, in which case it is referred to as “residual moisture” (RM). For example, sodium manganese ferrocyanoferrate (MnFeHCF) TMCCC material with the formula Na1.4MnII0.8FeIII0.2[Fe(CN)6]0.9(H2O)2.6 has n = 2.6 and RM = 14.5%. The RM of TMCCC can range from about 0 to about 25% or higher.

[0070] TMCCC materials possess an open-framework crystal structure in which the hexacyanate anion of formula R(CN)6-p(NC)p is octahedrally coordinated with the transition metal cation of substance P. This structure can be configured in a cubic phase or, less commonly, a rhombohedral or monoclinic phase. In the non-cubic phase, the R-CN-P bonds are off-axis, while in the cubic phase, the R-CN-P bonds are linear along the same axis.

[0071] The TMCCC structure contains large interstitial sites where mobile cations A+ and water can reside. Since A+ cations are not strongly bound to the lattice, they can readily leave and re-enter the structure during the electrochemical cycling of the TMCCC material. Similarly, uncoordinated water can reversibly leave and re-enter the TMCCC material. Uncoordinated water can be removed by exposing the TMCCC material to low ambient relative humidity (RH), by heating the material, by applying a vacuum to the material, by electrochemically or chemically inserting additional A+ cations into the material (and thus occupying interstitial spaces otherwise occupied by water molecules), or a combination of these or other processes. Regardless of the specific drying method, water will leave the TMCCC material until an equilibrium RM is reached. Conversely, exposing a "dry" TMCCC material with a low RM to moisture by contacting liquid water or by exposure to an atmosphere with high RH will cause the material to absorb water until a new equilibrium is reached at a higher RM. For many TMCCC materials, non-coordinated water can be easily removed by drying the material in air or under vacuum at a temperature of 60-130°C.

[0072] TMCCC materials also contain water bound to the framework structure. The most common configuration of bound water is water coordinated to the P-site cation at a neighboring hexacyanometalate vacancy (for z < 1). The presence of this vacancy includes the absence of a CN group, thus a vacancy exists in the coordination shell of each of the adjacent P-site cations. The synthesis of TMCCC materials is typically carried out in water, allowing ambient water molecules to bind to the P-cations to fill the vacancies in their coordination shells (generated by hexacyanometalate vacancies).

[0073] Consider an example of lattice-bound water, where the TMCCC structure lacks the central R(CN)6 group, and each of the six adjacent P-site cations is coordinated to a water molecule. In this TMCCC material, uncoordinated water may or may not be coordinated with interstitial sodium ions, and in the lattice-bound water, each P-site cation adjacent to the R(CN)6 vacancy has a water molecule bonded to it. If the lattice-bound water is removed by an aggressive drying process, these P-site cations will be unstable because their coordination shells are no longer filled. This leads to a less stable structure and reduced performance of the TMCCC electrode.

[0074] TMCCC materials can be processed into composite battery electrodes in a variety of ways. These composite battery electrodes may also include one or more conductive additives (e.g., carbon) and one or more polymer binders. A general method involves mixing TMCCC with carbon and binders in one or more organic solvents to form a viscous slurry or ink that can be coated onto a substrate. This mixing can be carried out at low or high shear rates to optimize the dispersion of TMCCC, carbon, and binders in the solvent. After mixing, the resulting slurry can be coated onto a substrate such as a mesh or foil. These substrates can be metals, such as aluminum, copper, or stainless steel, or surface-modified metals, such as carbon-coated aluminum. Coating can be performed using a roller coater, a die coater, an extrusion coater, or other types of coaters. After coating, the coated substrate is dried by one or more of the following methods: convection heating, infrared heating, convective airflow, or other drying processes. The result of the drying process is a composite electrode on the substrate. The drying step performed after coating to form the composite electrode is primarily for the purpose of evaporating the solvent present in the slurry. This drying step may optionally reduce the RM of the TMCCC material present in the coated electrode.

[0075] The composite electrode can then be densified using a rolling mill, such as a calender. Variations in the electrode fabrication process can be used to achieve enhanced electrode performance. These variations may include selecting various conductive carbons or combinations thereof, including but not limited to carbon black, graphite, or hard carbon, or selecting various binders or combinations thereof, including but not limited to vinyl fluoride / hexafluoropropylene copolymers, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene, or styrene-butadiene rubber-based polymers. Variations in the electrode fabrication method may also include the temperature, duration, and pressure during the electrode drying process.

[0076] The drying process can be carried out on the TMCCC material including the first RM. The drying process can include heating, exposure to vacuum, or both. It is desirable to dry at temperatures below 130°C, preferably below 100°C, to selectively remove non-coordinated water rather than lattice-bound water. The drying process can also be carried out using a combination of heating and exposure to vacuum, where vacuum is defined as an ambient pressure less than 1 bar, preferably less than 0.1 bar. The drying process causes the RM of the electrode to decrease to a value less than its first RM, typically to a second RM of about 1% to about 10%. The rate at which drying proceeds from the first RM to the second RM depends on the temperature and vacuum pressure. Advantageously, drying is carried out at a relatively slow rate at temperatures below 100°C, allowing the drying process to be stopped at a fully controlled second RM. In this case, the drying can be carried out for a duration of 10 minutes to 1 hour, or 1 hour to 10 hours, or 10 to 20 hours. Drying the TMCCC material for about 1 hour or longer, preferably 10 hours or longer, results in a uniform drying process: all TMCCC material particles in the sample reach the same RM, and water in these particles can be uniformly distributed. Prolonged exposure of TMCCC materials to temperatures of 100°C or higher for 20 hours or longer can lead to chemical instability and undesirable chemical reactions. Therefore, the drying rate to the desired second RM should be slow enough to ensure uniform drying to the precise second RM, but not so slow that undesirable chemical reactions may occur. These considerations regarding the drying rate also apply to the vacuum pressure applied during drying. The stronger the vacuum, the faster the drying will occur at any given temperature. Therefore, the vacuum pressure should be selected in conjunction with the drying temperature to obtain the desired drying rate and uniformity, as well as the desired RM. These considerations apply not only to the drying process on TMCCC materials but also to processes on one or more electrodes containing one or more TMCCC materials, or on battery stacks containing one or more such electrodes.

[0077] The drying process can be carried out on electrodes comprising one or more TMCCC materials, each TMCCC material comprising one or more first RMs, which are then assembled into a battery stack. The drying process can include heating, exposure to a vacuum, or both. For electrodes containing TMCCC materials, temperatures below 130°C, preferably below 100°C, are desirable to allow the removal of non-coordinated water rather than lattice-bound water. This results in the electrode's RM decreasing to a value less than its initial RM, typically to a second RM of about 1% to about 10%. Composite electrodes containing polymer binders are typically calendered to reduce their porosity to the desired value. Doing so allows for batch-to-batch control of the electrode's porosity, density, and thickness, enabling the fabrication of reliable, high-quality battery designs. However, calendering involves mechanical deformation of the electrode, which can induce stress within the composite layer. When the polymer is heated, its Young's modulus and yield strength decrease. This weakening of the polymer binder during the heating process associated with the electrode drying process can allow stress release through electrode deformation. One type of electrode deformation is curling, where the edges of the originally planar porous electrode curl toward each other. Curling can be irregular, making electrode stack assembly challenging and prone to defects. To reduce electrode curling, a stack of one or more perforated electrodes can be placed between two compression plates. These plates limit electrode deformation during drying. By preventing curling and by maintaining the planar structure of each electrode, each electrode is exposed to the same drying conditions (temperature and local vacuum pressure), thus achieving a uniform RM for all electrodes present during drying. Electrodes can also be separated from each other by thin spacers made of metal, plastic, or another material that is flat and chemically inert under drying conditions (temperature and vacuum pressure). These dried electrodes can then be assembled into a battery using standard processing steps, such as stacking one or more anode electrodes, separators, and cathode electrodes to form a battery stack. To ensure that the electrodes no longer absorb water to achieve a third RM greater than the second RM obtained at the end of the drying process, each subsequent processing step should be performed at a low, controlled RH until the battery stack is sealed in an impermeable battery pack.

[0078] A battery stack can be assembled by placing one or more anode electrodes, separators, and cathode electrodes into a multilayer stack. These one or more layers can be arranged such that separators are placed between each electrode layer, and furthermore, that every other electrode layer is either an anode or a cathode. The result of this stacking process can be an arrangement of layers, such as…anode, separator, cathode, separator,…, such that a separator placed between two electrodes is adjacent to both an anode electrode and a cathode electrode. The first and last layers in the stack can be electrodes of the same or opposite types, or they can be separators, or they can be both electrodes and separators. Discrete electrodes and separators can be placed adjacent to each other to form a multilayer stack (see figure). Alternatively, a single long separator can be folded or woven back and forth between alternating anode and cathode electrodes (see figure).

[0079] After assembling the battery stack, a first tab is attached to one or more anode layers, and a second tab is attached to one or more cathode electrodes. These tabs are typically designed to protrude beyond the battery package to allow for electronic contact with the battery. The tab attachment process can be performed by ultrasonic welding, electro-spot welding, laser welding, chemical bonding with an electronically conductive adhesive, or by one or more other processes that result in tight contact and electronic conductivity between the tab and one or more electrodes. After attaching the tabs, the battery stack can be placed in a package that is impermeable to air, water, or other chemical contaminants. One or more liquid electrolytes can be placed in the package containing the battery stack. After all internal battery components are placed inside the package, the package is sealed. The package can include a multilayer polymer / metal laminate, a metal can or box, or a metal can or box lined with electronic insulation, or another type of packaging material that is impermeable to water and air. The package can be sealed by performing a heat-sealing process, a laser welding process, or one or more other sealing processes. A sealing process can be performed such that the only components of the battery extending from the inside of the package to the outside are the two tabs.

[0080] Crucially, to maintain the required second RM for one or more electrodes, each subsequent processing step up to the sealing of the battery pack must be performed under controlled low RH conditions. If one or more electrodes or one or more battery stacks are exposed to uncontrolled or high RH, they can reabsorb water, resulting in a third RM greater than the desired second RM. The process requirement of controlled low RH can increase the cost and complexity of the manufacturing process, or it can reduce the process's throughput or yield.

[0081] The drying process can also be performed on a battery stack containing one or more anode electrodes, spacers, and cathode electrodes. This battery stack drying process can be performed on a battery stack containing electrodes that have been pre-dried to achieve the desired second RM as described above, or on a battery stack containing electrodes that have not been pre-dried. The electrodes present in the battery stack can be rolled before stack assembly and can include deformation and internal stress. Therefore, performing a drying process on the battery stack without mechanical restraint can result in curling of the electrodes within the battery stack. This curling of the electrodes within the battery stack can be greater than, approximately equal to, or less than the curling that occurs during the drying of one or more unrestrained electrodes (as described above). To minimize or eliminate the curling of the electrodes within the battery stack during drying to the desired second RM, one or more battery stacks can be mechanically restrained between two compression plates. Spacers can optionally be placed between the battery stacks. By mechanically restraining the battery stacks, electrode curling can be eliminated and the planar structure of the electrodes can be maintained. This allows for a consistent drying process, where a uniform second RM is achieved for each anode and cathode in each battery stack.

[0082] The change in RM of one or more anode electrodes can be expressed as ΔRM(a), where ΔRM(a) is equal to the difference between the first RM, denoted as RM(a1), and the second RM, denoted as RM(a2): ΔRM(a) = RM(a1) - RM(a2). Similarly, the change in RM of one or more cathode electrodes can be expressed as ΔRM(c), where ΔRM(c) is equal to the difference between the first RM, denoted as RM(c1), and the second RM, denoted as RM(c2): ΔRM(a) = RM(c1) - RM(c2). As mentioned above, the first RM, such as RM(a1) or RM(c1), depends on the composition of the TMCCC material and the conditions under which it reaches equilibrium, such as RH and temperature. The second RM, such as RM(a2) or RM(c2), depends on one or more conditions of the drying process, such as temperature, vacuum pressure, and duration.

[0083] When each of RM(a1) and RM(c1) is greater than each of RM(a2) and RM(c2), or in other words, when RM(a1), RM(c1) > RM(a2), RM(c2), each of ΔRM(a) and ΔRM(c) is greater than zero. In this case, a net amount of water is removed from both one or more anodes and one or more cathodes, resulting in a net reduction of water across the entire stack. Therefore, this stack drying process is equivalent to a cell manufacturing process including separate electrode drying processes, wherein said separate electrode drying processes comprise drying a first number of one or more anode electrodes to RM(a2) in a first process, and drying a second number of one or more cathode electrodes to RM(c2) in a second process, followed by stacking at a low controlled RH to form a cell stack. Therefore, performing a single drying process on a fully assembled cell stack enables a single process to be carried out, and can eliminate the process requirement for a low controlled RH for cell assembly steps performed between electrode drying and sealing of the cell package.

[0084] When the stack drying process is performed under the condition of RM(a1)<RM(a2)<RM(c2)<RM(c1), a net amount of water can be removed from the stack, and some water can be transferred from one or more anodes to one or more cathodes. Similarly, if the stack drying process is performed under the condition of RM(c1)<RM(c2)<RM(a2)<RM(a1), a net amount of water can be removed from the stack, and some water can be transferred from one or more cathodes to one or more anodes. Achieving desired RM(a2) and RM(c2) through the combination of water transfer between one or more anodes and one or more cathodes requires a smaller total net water loss from the electrodes. Where a smaller total net water loss is required to obtain one or more second RMs, one or more drying processes can be performed at a lower temperature, under a lower vacuum pressure for a shorter duration, or have one or more other reductions in the intensity, cost or complexity of said drying processes.

[0085] When RM(a2) and RM(c2) are reached under the same drying conditions and one or more anodes and one or more cathodes are in communication with each other, RM(a2) and RM(c2) are in equilibrium. If RM(a2) and RM(c2) are in equilibrium, there is no thermodynamic driving force for water to move from one type of electrode to another. If battery assembly processing steps are performed after the battery stack drying process such that RM(a2) and RM(c2) are not altered, they can remain in equilibrium with each other during these drying processes, and further, during battery operation. If RM(a2) and RM(c2) remain in equilibrium with each other during battery operation, water may not be released from one or more electrodes to undergo undesirable chemical or electrochemical reactions. Therefore, drying the battery stack, rather than drying individual electrodes, can improve battery performance.

[0086] Example

[0087] For each of the following embodiments, a porous electrode containing TMCCC material is manufactured by first mixing TMCCC powder, nanoparticle carbon black powder, and styrene-butadiene binder in a solution of xylene and butanol at a mass ratio of approximately 85:7.5:7.5 to form a viscous slurry. This slurry is then coated onto an aluminum foil substrate using a die coater to form a coated electrode with a target solid mass loading of approximately 20 mg / cm². The coated electrode is heated at a temperature not exceeding 100°C for 10 minutes to remove the organic solvent, thereby forming a dry electrode with a first porosity exceeding 50%. The dried electrode is then calendered to a second porosity of less than 30% to form a porous electrode. The porous electrode is then punched into sheets of desired sizes (approximately 2 × 2 cm to approximately 20 × 20 cm) for use in battery packs with various shape factors, thereby forming a perforated anode electrode.

[0088] 1. Drying of a single-layer electrode

[0089] The anode and cathode can be dried at the electrode level to obtain optimal RM.

[0090] Example 1

[0091] Anode electrodes were prepared. The prepared anodes contained 9.1% of the first RM, as measured using a Karl Fischer volumetric titrator. Six 15 cm² anode electrodes were placed in a monolayer on a central rack in a vacuum oven preheated to 70°C. The vacuum oven was evacuated, and the electrodes were dried under dynamic vacuum for 20 minutes, reaching a final pressure of 0.67 Torr in the vacuum oven after 20 minutes. The oven was then refilled with nitrogen, and the anode electrodes were removed from the oven. The dried anodes contained a second 7.1% RM based on the mass of the electrode complex, as measured using a Karl Fischer volumetric titrator.

[0092] Example 2

[0093] Cathode electrodes were prepared. The prepared cathodes contained 18.2% first RM, as measured using a Karl Fischer volumetric titrator. Six 15 cm² cathode electrodes were placed in a monolayer on the center rack of a vacuum oven preheated to 110°C. The vacuum oven was evacuated, and the electrodes were dried under dynamic vacuum for 60 minutes, reaching a final pressure of 0.37 Torr in the vacuum oven after 60 minutes. The oven was then refilled with nitrogen, and the cathode electrodes were removed from the oven. The dried cathodes contained 6.9% second RM, as measured using a Karl Fischer volumetric titrator. The dried anode and cathode electrodes were then stacked into a cell under humidity control. The resulting cell exhibited optimal performance.

[0094] The following are used for preparation Figure 1-4 The data shown is a dry, general paragraph of this type.

[0095] Anodes are typically dried at temperatures ranging from 60°C to 100°C, while cathodes, which naturally contain more water than anodes, are typically dried at temperatures ranging from 100°C to 120°C. Care must be taken to avoid drying at high temperatures that would cause thermal degradation of the electrodes or active materials. Therefore, it is important to understand the thermal characteristics of the electrode assembly before developing a drying method. For two electrodes, the drying duration typically ranges from 20 minutes to 2 hours. For two electrodes, the final pressure achieved in the vacuum oven during drying is typically in the range of 0.2–1.0 Torr. The RM of the undried electrode, the residual slurry solvent content in the undried electrode, and the vapor pressure of the aforementioned volatiles will significantly influence the drying temperature and duration required to achieve optimal RM for each electrode. These factors can vary depending on the powder synthesis conditions, slurry composition, and slurry coating and drying conditions. Additionally, the batch size of the drying batch or the total mass of the electrodes in the vacuum oven during a drying cycle will alter the drying temperature and duration required to achieve optimal RM.

[0096] 2. Powder drying

[0097] Another way to achieve optimal RM in the final product is to perform a drying step at the powder level upstream of the electrode.

[0098] Example 1

[0099] Synthetic anode powder. The synthesized anode powder contained 8.7% first RM, as measured by a Karl Fischer volumetric titrator. 20 g of anode powder was spread in a glass dish and covered with a Kim wiping agent secured to the glass container using a rubber band. The glass container was placed in the center rack of a vacuum oven preheated to 70°C. The anode powder was dried under dynamic vacuum for 16 hours. The dried anode powder contained 7.1% second RM, as measured by a Karl Fischer volumetric titrator.

[0100] Example 2

[0101] Cathode powder was synthesized. The synthesized cathode powder contained 16.3% first RM, as measured by a Karl Fischer volumetric titrator. 20 g of cathode powder was spread in a glass dish and covered with a Kim wiping agent secured to the glass container with a rubber band. The glass container was placed in the center rack of a vacuum oven preheated to 100°C. The cathode powder was dried under dynamic vacuum for 16 hours. The dried cathode powder contained 7.0% second RM, as measured by a Karl Fischer volumetric titrator.

[0102] Commentary after the powder drying process:

[0103] The dried powder is then mixed with conductive additives and a binder to form a slurry, which is then coated onto the electrode sheet. The slurry formulation is adjusted to account for the different rheological properties of the dried powder compared to its typical undried state. The coated electrodes are then dried at low temperature to evaporate the slurry solvent. The resulting electrodes contain optimal moisture content and do not require additional vacuum drying. The electrodes are then stacked to form a battery exhibiting optimal performance. This drying approach requires all subsequent processing steps after vacuum drying of the powder to be carried out in a moisture-controlled environment, ensuring that the dried powder remains under optimal RM conditions and does not reabsorb moisture from the processing environment.

[0104] 3. Electrode Stack Drying Process - General Example

[0105] Example 1: Electrode Drying. Electrode stacks comprising 5-30 sheets were prepared and weighed. Depending on the material, batch size, and desired target residual moisture, the electrodes were dried in a vacuum oven under dynamic vacuum at a temperature between 80 and 120°C for 90 to 480 minutes.

[0106] Example 2: Electrode Drying. A stack of no more than 30 electrodes was placed in a vacuum oven, and preheated plates, each weighing at least 2 pounds, were placed on top of the electrode stack. Depending on the material, batch size, and required residual moisture content, the electrodes were dried under dynamic vacuum at a temperature of 80-120°C for 90 to 480 minutes.

[0107] Applying pressure or constricting the electrodes in a stack to improve the uniformity of heat transfer in a stack with multiple electrodes can be advantageous. This can be achieved by using a thick plate with a surface area similar to that of the electrodes, or by a fixing device that places the electrodes between plates bolted together to provide the required amount of pressure.

[0108] The electrodes can be dried equivalently in a vacuum oven or in a convection oven under an inert atmosphere such as nitrogen.

[0109] Example 3: Electrode Drying. Electrodes containing a first RM1 > 13.4% were dried in a vacuum oven at 120°C under dynamic vacuum for 360 to 600 minutes, depending on batch size, until a second RM2 < 6.7%. The electrodes were then stacked into cells at a controlled RH of < 10%. Measurements taken after cell stacking showed that these electrodes had reached a third RM3 between 6.7% and 7.2%, where RM3 > RM2, and RM3 is the desired final material moisture content.

[0110] Example 4: Electrode Drying. The electrodes were placed in a convection oven at a temperature of 80-120°C, and the oven was purged with N2 at a rate of up to 150 SCFM during drying. The electrodes were dried for 50-90 minutes, depending on the material, batch size, and required residual moisture.

[0111] 4. Electrode Stack Drying Process - Specific Implementation Examples

[0112] Example 5: Cathode Electrode Drying. The residual moisture content of the cathode electrode comprising sodium manganese iron hexacyanoferrate (TMCCC) material was measured to be 18.4% of the electrode composite mass using a Karl Fischer apparatus. Stacks of 14 cathode electrodes (approximately 385 cm²) were placed horizontally on two shelves of a vacuum oven, evenly spaced. These stacks were covered with approximately 500 g of aluminum plate. Both the oven and the plate were preheated to 120°C. The electrodes were dried under active vacuum for 6 hours. The final moisture content, measured by a Karl Fischer apparatus, was 7.0% of the electrode composite mass.

[0113] Example 6: Anode Electrode Drying. The residual moisture content of the anode electrode comprising sodium manganese hexacyanomanganate (TMCCC) material was measured to be 8.1% of the electrode composite mass using a Karl Fischer apparatus. Stacks of eight to twelve anode electrodes (approximately 369 cm²) were placed horizontally and evenly spaced on two shelves of a vacuum oven. These stacks were covered with approximately 500 g of aluminum plate. Both the oven and the plate were preheated to 80°C. The electrodes were dried under active vacuum for 80 minutes. The final moisture content was measured to be 7.1% of the electrode composite mass using a Karl Fischer apparatus.

[0114] Battery drying method - general embodiment

[0115] Example 7: Battery Drying. Batteries consisting of stacked anode and cathode electrodes with spacers and placed inside an unsealed laminated package can be arranged in a single layer or stacked 2-3 batteries high, and dried in a vacuum oven. The batteries are dried under dynamic vacuum at 95°C for 60-120 minutes, depending on batch size and desired target residual moisture.

[0116] It may be advantageous to dry the stacked cells as a single unit, rather than drying individual electrodes or multiple anode or cathode electrodes, to improve the efficiency, yield, or cost of the drying process and downstream processes (collectively, manufacturing considerations), or to achieve the desired final RM.

[0117] For manufacturing considerations, or to achieve the desired final moisture content (RM), it may be advantageous to pre-dry one or more anode or cathode electrodes before battery assembly, followed by drying the fully assembled battery stack. In some cases, one electrode can be pre-dried from a first RM to a second RM, and then dried to a third RM during the battery drying step, which may be larger or smaller than the second RM, due to moisture transfer between the anode and cathode electrodes during the battery drying step. In this way, the final moisture target for both electrodes can be designed and achieved through complementary drying steps.

[0118] Furthermore, due to manufacturing considerations or the desired final material humidity, it may be advantageous to select drying conditions that remove more water from the electrode material than the desired final target when moisture reabsorption is anticipated in subsequent processing steps.

[0119] 5. Battery Drying Process - Specific Implementation Examples

[0120] Example 8: Cell Drying. A large number of stacked cells of eight were prepared in unsealed laminated bags. Representative electrode samples were measured using Karl Fischer measurements prior to drying. The cathode was found to have a first RM (RMc(1)) of 18.4%, and the anode was found to have a first RM (RMa(1)) of 8.1%. The cells were loaded into a vacuum oven and covered with an aluminum compression plate weighing approximately 500 g. Both the oven and the plate were preheated to 90 °C. The cells were dried under active vacuum for 90 minutes and then removed from the oven. The cells were disassembled, and samples were taken for Karl Fischer moisture measurements. The second RM of the electrodes was measured. For the cathode, the second RMc(2) was measured to be 14.0%, while for the anode, the second RMc(2) was measured to be 5.8%. A net decrease in RM was observed for each of the two electrodes.

[0121] 6. General concepts of the embodiments:

[0122] 1. Equipment Construction

[0123] The drying system consists of a vacuum oven connected to a vacuum pump, with a solvent trap between the oven and the pump along the vacuum line. A digital pressure gauge is used to accurately monitor the pressure achieved in the vacuum oven during drying. Before drying, the oven should be preheated and stabilized at the required temperature, and the solvent trap must be pre-frozen. Under full vacuum with pre-frozen solvent trap and preheated oven, when the oven is empty, a pressure of <0.2 Torr should be obtained. This confirms that all seals in the system are acceptable.

[0124] 2. Reabsorption

[0125] Dried electrodes are very hygroscopic and tend to reabsorb moisture from their environment. Specifically, when contacting another electrode during cell stacking, electrodes can reabsorb moisture from moisture in the air, or they can absorb moisture from that electrode.

[0126] When reabsorption of moisture by the electrodes from humid air is expected in the downstream process, it may be advantageous to pre-dry the electrodes to moisture content lower than the optimal RM.

[0127] It may be advantageous to dry a set of electrodes to moisture a < b, where b is the optimal RM of the electrodes (anode or cathode) of this set, and then stack the set of electrodes into a cell, wherein other electrodes have moisture x > y, where y is the optimal RM of the electrodes (anode or cathode) of the other set. Moisture transfer between electrodes during cell stacking can allow both sets of electrodes to reach their optimal RM of b and y. If moisture transfer from cell stacking is insufficient, subsequent drying of the cell stack can enhance moisture transfer between the electrode sets.

[0128] Figure 1 shows the specific capacity of electrodes containing sodium manganese hexacyanomanganate TMCCC anode material, as a function of residual moisture in the electrodes after drying;

[0129] Figure 2 shows the total impedance and charge transfer resistance of electrodes containing sodium manganese hexacyanomanganate TMCCC anode material, as a function of residual moisture in the electrodes after drying;

[0130] Figure 3 shows the electrochemical impedance spectroscopy of electrodes containing sodium manganese hexacyanomanganate TMCCC anode material, as a function of residual moisture in the electrodes after drying;

[0131] Figure 4 shows the total impedance and charge transfer resistance of electrodes containing sodium manganese iron hexacyanoferrate TMCCC cathode material, as a function of residual moisture in the electrodes after drying;

[0132] Figures 1 to 3 The results show that the specific capacity of the anode electrode decreases for a drier, lower RM electrode. Furthermore, the total impedance and charge transfer resistance increase for a drier, lower RM anode. This indicates that the lower the RM, the greater the performance degradation of the anode electrode.

[0133] Figure 4 The results show an increase in total impedance and charge transfer resistance for drier, lower RM cathodes. As demonstrated by the increase in total impedance and charge transfer resistance, performance degradation begins for the cathode below 3% RM and for the anode below 7%. This indicates that the drying conditions for optimizing the performance of TMCCC electrodes depend on the composition of the TMCCC material contained in the electrode.

[0134] Figure 5 The specific capacity of the capacity-limiting electrodes of a full cell comprising a sodium manganese hexacyanomanganate TMCCC anode and a sodium manganese iron hexacyanomanganate TMCCC cathode is shown. The capacity decreases as the weighted average residual moisture of the two electrodes decreases;

[0135] Figure 6 The power density and energy density of the capacitively limited electrodes of a full cell comprising a sodium manganese hexacyanomanganate TMCCC anode and a sodium manganese iron hexacyanomanganate TMCCC cathode are shown. Both power density and energy density decrease with decreasing weighted average residual moisture of the two electrodes;

[0136] Figure 7 Electrochemical impedance spectroscopy (EIS) of a full cell comprising a sodium manganese hexacyanomanganate TMCCC anode and a sodium manganese iron hexacyanoferrate TMCCC cathode is shown as a function of the weighted average residual moisture content of the two electrodes.

[0137] Figure 8 The lifespan of a full cell comprising a sodium manganese hexacyanomanganate TMCCC anode and a sodium manganese iron hexacyanoferrate TMCCC cathode is shown during a float test at 45°C. In this test, the cells were continuously floated at a maximum voltage of 1.859V and fully discharged once daily at a rate of 1C. The cell with the lowest weighted average residual moisture was the most stable and had the longest lifespan.

[0138] Figures 5 to 7 The trend observed for individual cathodes and anodes is shown to also apply to full cells. The drier the electrodes in a full cell, the lower the cell's capacity, power, and energy, and the higher their impedance. However, Figure 8 This demonstrates that the longest battery life is achieved by a battery containing the driest electrodes. Therefore, the optimal battery would contain electrodes with an intermediate amount of residual moisture, which strikes an optimal balance between performance metrics such as battery life (favorable to drier electrodes) and high capacity and low resistance (favorable to more wetted electrodes).

[0139] Figure 9 The initial and final residual moisture, coordinated water, and non-coordinated water of the selected examples are shown in tabular form. In each case, non-coordinated water is reduced during sample processing, which includes a dehydration step. The temperature used during the dehydration step does not exceed 120°C, which allows for the selective removal of non-coordinated water from the TMCCC sample without removing coordinated water.

[0140] To determine the composition of each TMCCC material, inductively coupled plasma (ICP) and Karl Fischer (KF) analyses were performed. ICP data were analyzed using KF data for oxygen values, and then charge balance was forced to the known initial charge state of the TMCCC material. It was then assumed that the coordinated water content was proportional to the vacancy mole fraction. The non-aqueous content of the material was expressed on a 100% mass basis, and water was expressed as an additional mass percentage based on this basis. The KF values ​​measured by the electrodes were converted from total electrode mass % to a water mass percentage reflecting the mass of non-aqueous TMCCC as a function of sample weight (regardless of water content), always normalized to 100%. The stoichiometric ratio of coordinated and non-coordinated water was used to determine the proportion of undried water measured by KF. For these calculations, it was assumed that all non-coordinated water was removed during the drying process before any coordinated water was detected.

[0141] Figure 10 Exemplary compositions of two TMCCC materials on a molar basis are shown in tabular form, and exemplary calculations of residual moisture are provided from these molar compositions on a mass percentage basis. Coordinated water is proportional to the vacancy content of each TMCCC material, while non-coordinated water depends on the synthesis and processing conditions prior to composition measurement.

[0142] in conclusion

[0143] References [2] and [3] teach that any trace amount of water in cells leads to reduced battery performance. Embodiments of the present invention are considered novel and non-obvious, at least in part because drying the TMCCC electrode to a non-zero RM, within which the presence of some water in the material actually improves battery performance, thus allowing for optimization.

[0144] The concept of a single dehydration / hydration process on a fully assembled battery stack is also considered novel and non-obvious. This process is practical, at least in part, because it aims to achieve a non-zero equilibrium RM (water affinity). This is because the composition of the TMCCC material determines its affinity for water and reaches an equilibrium RM under specific ambient temperatures and pressures. When two electrodes (each containing a unique TMCCC material) are placed close to each other, the electrode with a higher affinity for water and a higher equilibrium RM will absorb water from the other electrode until they both reach equilibrium. Therefore, performing a drying / hydration step on a battery stack containing two TMCCC electrodes can result in water being transferred from one electrode to the other, in addition to the net water loss observed during conventional drying processes. This water transfer between electrodes can further degrade the performance of the electrochemical cell.

[0145] Therefore, performing a single drying step on the battery stack is advantageous for two reasons. First, it is a simpler process than performing separate drying steps on each of the two electrodes before assembling them into the battery stack. Second, the single drying step results in a net loss of water throughout the battery stack (net drying) and also a net transfer of water between the two electrodes until they reach equilibrium with each other. Chemical equilibrium represents the most stable state of a system under a specific set of conditions (temperature, pressure, etc.). The battery stack in which each of the two electrodes contains an equilibrium amount of water is the most stable, and the minimum possible amount of water will be chemically active. Therefore, by equilibrating the two electrodes with each other via a single drying step, optimal RM for optimal battery performance can be achieved, while simultaneously reaching an equilibrium where the RM of each of the two electrodes is the most chemically stable and at least reactive.

[0146] Figure 9 The residual moisture, coordinated water, and non-coordinated water of the selected examples described herein before and after drying are shown. By expressing residual moisture in this way, the water content in the material composition can be discussed. Figure 10 The selected compositions of the examples described herein are shown. For both the anode and cathode, the composition of the materials is in moles. Furthermore, residual moisture, coordinated water, and non-coordinated water are calculated based on mass percentages. Therefore, the residual moisture measured for each sample in the specification relates to the composition of the TMCCC material for those examples. For example, the composition of the anode synthesized as is included in the original sample composition with n = 1.6 and m = 1.1 (following the description of the composition used herein). In this case, m = 1.1 corresponds to 7% non-coordinated water in the original synthesized material. This decreases during processing as described herein. For example, in Example 1, the final non-coordinated water content is 6.1%, which corresponds to m = 0.96.

[0147] The initially manufactured TMCCC material may contain non-coordinated water in the range of approximately 5-15%, corresponding to approximately m = 1.0 to 2.0. Figure 10The diagram shows that for each embodiment including post-treatment, the non-coordinated water is reduced to about 0-10%, or equivalently to about m = 0 to 1.5.

[0148] References - explicitly cited herein as references:

[0149] Reference [1]-Imhof, R.In Situ Investigation of the ElectrochemicalReduction of Carbonate Electrolyte Solutions at GraphiteElectrodes.J.Electrochem.Soc.,145,1081-1087(1998)

[0150] Reference [2] - US9,099,718B2 (Lu'718)

[0151] Reference [3] - Wu, J, et al, J. Am. Chem. Soc., 139, 18358-18364 (2017).

[0152] The systems and methods described above have been generally outlined to aid in understanding the details of preferred embodiments of the invention. Numerous specific details, such as examples of components and / or methods, are provided in this description to provide a thorough understanding of embodiments of the invention. Some features and benefits of the invention are realized in such a mode and are not essential in every instance. However, those skilled in the art will recognize that embodiments of the invention can be implemented without one or more specific details, or with other means, systems, components, methods, parts, materials, etc. In other instances, well-known structures, materials, or operations have not been specifically shown or described in detail to avoid obscuring aspects of embodiments of the invention.

[0153] Throughout this specification, references to "an embodiment," "an embodiment," or "a particular embodiment" mean that a specific feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment of the invention, but not necessarily in all embodiments. Therefore, the phrases "in one embodiment," "in an embodiment," or "in a particular embodiment" appearing throughout this specification do not necessarily refer to the same embodiment. Furthermore, any particular feature, structure, or characteristic of any particular embodiment of the invention may be combined with one or more other embodiments in any suitable manner. It should be understood that, in view of the teachings herein, other variations and modifications of the embodiments of the invention described and illustrated herein are possible and are considered part of the spirit and scope of the invention.

[0154] It should also be understood that one or more elements shown in the figures / drawings may also be implemented in a more separate or integrated manner, or even removed or rendered inoperable in some cases, which may be useful depending on the specific application.

[0155] Furthermore, any signal arrows in the accompanying drawings should be considered merely exemplary and not limiting, unless otherwise specifically indicated. The combination of components or steps should also be considered when terms are intended to obscure the ability to separate or combine.

[0156] The foregoing description of the illustrated embodiments of the invention, including those described in the abstract, is not intended to be exhaustive or to limit the invention to the precise forms disclosed herein. While specific embodiments and implementations of the invention have been described herein for illustrative purposes only, various equivalent modifications are possible within the spirit and scope of the invention, as will be recognized and understood by those skilled in the art. As noted, such modifications can be made to the invention based on the foregoing description of the illustrated embodiments and will be included within the spirit and scope of the invention.

[0157] Therefore, although the invention has been described herein with reference to specific embodiments thereof, modifications, various alterations and substitutions are intended in the foregoing disclosure, and it should be understood that in some cases, some features of embodiments of the invention will be employed without correspondingly using other features, without departing from the scope and spirit of the invention as set forth. Thus, many modifications can be made to adapt particular situations or materials to the essential scope and spirit of the invention. It is intended that the invention be limited to the specific terminology used in the appended claims and / or the specific embodiments disclosed as the best mode for carrying out the invention, but rather that the invention will include any and all embodiments and equivalents falling within the scope of the appended claims. Therefore, the scope of the invention is defined only by the appended claims.

Claims

1. A method of manufacturing a battery stack for an electrochemical cell, the battery stack comprising a plurality of layers, each layer comprising an anode electrode, a cathode electrode, and a separator disposed therebetween, wherein all anodes in the plurality of layers are in electronic communication, and all cathodes in the plurality of layers are in electronic communication, and wherein at least one electrode comprises a coordination compound material, the coordination compound material comprising a water content, the water content comprising a set of electrochemical properties deteriorating when present during electrochemical cycling of the battery stack, the method comprising: a) Manufacturing a set of electrodes, wherein the entire set of electrodes comprises an anode electrode and a cathode electrode containing a coordination compound having the water content described above; b) Assemble a battery stack using the set of electrodes including the water content, the battery stack assembly b) producing an assembled battery stack having a subset of the electrodes including the water content; and c) Exposing the assembled battery stack having the set of electrodes including the water content to a water conditioning process configured to adjust the water content of the electrodes of the set of electrodes to within the adjusted water content; The adjusted water content includes a reduction in a set of electrochemical properties that are present during the electrochemical cycling of the assembled battery stack; The adjusted water content includes residual moisture of all electrodes in the group of electrodes, which is greater than or equal to 4%. and Wherein, when the residual moisture content of all electrodes in the set of electrodes is greater than or equal to 4%, the set of electrodes contains non-zero coordinated water and non-coordinated water. The electrode, which includes a coordination compound material with the adjusted water content, comprises the following formula: THE x P y [R(CN)6] z (H2O) n Where A is one or more alkali metal cations. Wherein P and R are one or more divalent or trivalent transition metal cations. Of which 0.5 <z<1, Where n = 6 * (1-z) + m, and where n > 0, Where 6 * (1-z) is the amount of lattice-bound water and m is the amount of uncoordinated water, and Where m ≥ 0 Where 0 ≤ x ≤ 2, and y = 1.

2. The method of claim 1, wherein the step of exposing the assembled battery stack occurs in an environmental control room configured to apply the water conditioning process to the assembled battery stack, and wherein the step of assembling the battery stack is performed outside the environmental control room.

3. A method for producing a battery stack for an electrochemical battery, the battery stack comprising a plurality of layers, each layer comprising an anode electrode, a cathode electrode, and a separator disposed therebetween, wherein all anodes in the plurality of layers are in electronic communication, and all cathodes in the plurality of layers are in electronic communication, and wherein each electrode comprises a coordination compound material having residual moisture outside a desired residual moisture distribution, the method comprising: a) Assemble the battery stack while the residual moisture in the electrodes of each electrochemical cell exceeds the desired residual moisture distribution; And afterwards: b) Exposing the battery stack to a water conditioning process to adjust the residual moisture content of the electrodes in each electrochemical cell to a desired residual moisture distribution greater than or equal to 4%; and When the residual moisture content of all electrodes is greater than or equal to 4%, the electrodes simultaneously contain non-zero coordinated water and non-coordinated water. The electrode comprising the coordination compound material comprises the formula: A x P y [R(CN)6] z (H2O) n Where A is one or more alkali metal cations. Wherein P and R are one or more divalent or trivalent transition metal cations. Of which 0.5 <z<1, Where n = 6 * (1-z) + m, and where n > 0, Where 6 * (1-z) is the amount of lattice-bound water and m is the amount of uncoordinated water. Where m ≥ 0; and Where 0 ≤ x ≤ 2, and y = 1.

4. The method according to claim 3, wherein the coordination compound material comprises a TMCCC material having a first amount of coordinated water and a second amount of non-coordinated water, wherein the residual moisture distribution comprises the first amount of coordinated water within a first target range, and wherein the residual moisture distribution comprises the second amount of non-coordinated water within a second target range.

5. The method of claim 4, wherein the anode electrode comprises the TMCCC material, and wherein the TMCCC material comprises manganese hexacyanomanganate.

Citation Information

Patent Citations

  • Transition metal hexacyanoferrate battery cathode with single plateau charge / discharge curve

    US9099718B2

  • Electrode material for negative pole for lithium secondary cell, electrode structure using said electrode material, lithium secondary cell using said electrode structure

    CN1287694A

  • Non-aqueous electrolyte secondary battery

    US20090286164A1